"Why Aren't You a Sassy Little Thing": The Effects of Robot-Enacted Guilt Trips on Credibility and Consensus in a Negotiation. Issue 5 (19th October 2016) - Stoll, Brett; Edwards, Chad; Edwards, Autumn
Abstract : Robots are becoming increasingly popular in social applications and have demonstrated effectiveness in a variety of contexts such as education, health, task management, and other complex cooperative roles. The purpose of this study was to examine human–robot interaction in a nonassistive environment: a negotiation scenario. Specifically, the authors examined what effect message appeals (guilt trip, no guilt trip) and robot agency (principal, agent) had on the negotiation outcomes and perceptions of credibility. Results indicated a significant main effect of agency and an interaction effect between agency and guilt messaging on perceptions of robot credibility such that participants rated a robot agent employing no guilt trips as more credible than one negotiating as principal or one utilizing guilt trips. Neither guilt nor agency had a significant effect on the overall concession of the negotiation task.